Design of Experiment Method – An Application in Improving Quality of Magnesium Hydroxide Produced from Natural Seawater Bittern - Le-Minh, Tam; Hoang Dong, Nam; Nguyen Tan, Dzung (Journal of Chemical Engineering Research Updates, 2021)
Seawater bittern is an important resource for production of magnesium hydroxide. It is particularly meaningful for countries of which long beaches and high temperatures are available as natural advantages. This production process bases on the main reaction between solutions containing magnesium and various alkaline agents. Among of precipitants, lime slurry is frequently used as an inexpensive reactant. However, the contamination of calcium in the final magnesium hydroxide is a major problem which limits applicability of this product in many fields required extremely high quality of magnesium hydroxide such as pharmaceuticals, and catalyst, etc. In this work, magnesium hydroxide with more than 99% purity will be recovered from natural seawater bitterns by using the design of experiment (DOE) method. Selected from nine potential factors, a full factorial design considering four main effects was applied to construct a second-order regression model which allows predicting favorable conditions to pursuit high purity of magnesium hydroxide from multi-component seawater bittern and lime milk. On the one hand, the results for a 1.0 L batch investigation proved that factors such as concentration of Ca(OH)2 in lime suspension and residence time have strong negative influences on the product purity, besides positive effects of reaction temperature. On the other hand, magnesium concentration in the bittern was absent in the regression model. At the optimal conditions, the chemical purity of the solid product was obtained at a value of 99.35%. Thus, this product, and therefore its corresponding production conditions, can be recommended for applications required high quality of magnesium hydroxide.